REPAIR OF LOUDSPEAKERS AS A SUPPORT FOR WORSHIP ACTIVITIES AT THE AL-MADINAH AL-MUNAWWAROH PERUM MOSQUE. SUNRISE GARDEN BUKIT PUTRA CILEUNGSI WEST JAVA: PERBAIKAN PENGERAS SUARA SEBAGAI PENUJANG KEGIATAN IBADAH DI MASJID AL-MADINAH AL-MUNAWWAROH PERUM. SUNRISE GARDEN BUKIT PUTRA CILEUNGSI JAWA BARAT - Rismen Sinambela; Ito Khikmatulloh; Aldul Rahman; Yosep Hendriyana (Yayasan Education and Social Center, 2022)
Mosque loudspeakers or mosque speakers are an electronic device used to increase the sound intensity in mosques. Usually, each mosque has two loudspeaker systems, namely inside and outside. External loudspeakers are generally used for adhan and iqomah, while for others such as prayers, lectures and tadarus only use internal speakers. However, in several areas, a number of mosques, regardless of their neighbors who live nearby, also use their external loudspeakers for various activities other than the call to prayer and iqomah, which creates problems in society. Scientists, including those from Harvard University, found that besides causing hearing loss, noise pollution can also reduce intelligence, memory, mental health, lead to cardiovascular disorders (heart disease and stroke), type 2 diabetes mellitus, etc